New Era of Mapping and Understanding Common Fragile Sites: An Updated Review on Origin of Chromosome Fragility - Ji, Fang; Zhu, Xinli; Liao, Hongwei; Ouyang, Liujian; Huang, Yingfei; Syeda, Madiha Zahra; Ying, Songmin (Frontiers in Genetics, 2022)
Common fragile sites (CFSs) are specific genomic loci prone to forming gaps/breakages upon replication perturbation, which correlate well with chromosomal rearrangement and copy number variation. CFSs have been actively studied due to their important pathophysiological relevance in different diseases such as cancer and neurological disorders. The genetic locations and sequences of CFSs are crucial to understanding the origin of such unstable sites, which require reliable mapping and characterizing approaches. In this review, we will inspect the evolving techniques for CFSs mapping, especially genome-wide mapping and sequencing of CFSs based on current knowledge of CFSs. We will also revisit the well-established hypotheses on the origin of CFSs fragility, incorporating novel findings from the comprehensive analysis of finely mapped CFSs regarding their locations, sequences, and replication/transcription, etc. This review will present the most up-to-date picture of CFSs and, potentially, a new framework for future CFSs research.